Snap-Fit Joinery System Using Pinewood Material Elasticity Properties - MY Alief Samboro; Djoko Kuswanto (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
The elasticity of pinewood gives it the potential to be applied in a snap-fit system, a connection system that utilizes the elasticity of a material to connect separate parts to one another. This research was aimed at finding the right shape of the stress-relievers for pinewood snap-fit modules. An experiment was performed using a computer-numerical-control (CNC) router for fabrication with detailed precision.